THE HIDDEN GEMS IN PERPUSTAKAAN NEGARA MALAYSIA - Rabiah Mohd Ali; Nordiana Mohd Nordin; Mazlina Pati Khan , (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Rare books are special collections that hold historical, cultural, and intellectual value. This national intellectual heritage remains intricate in any institution and prohibits collections from accessing rather than other general collections. But the evolution of digital technology has made this collection available throughout the world 24/7. Perpustakaan Negara Malaysia carefully shifted to a broad perspective by moving forward on a challenging path from time to time. It includes strategic planning in the acquisition, preservation and conservation, digitisation, and promotion of the collections so they can provide information and materials to the patrons without any hassle. There are three objectives of establishing the Perpustakaan Negara Malaysia: making available for the use of present and future generations a national collection of library resources, facilitating nationwide access to library resources available within the country and abroad, and lastly, providing leadership on matters of libraries. “Koleksi Nadir” is referred to rare collections, and these collections have been classified as one of the special collections in the Perpustakaan Negara Malaysia. The values of these collections are beyond dollars and cents. It is proof of the Malaysian heritage and provides the society with knowledge and information that are beyond what is already known by the public. The collections are precious and access to this information can broaden new perspectives from many angles.